Three dimensional printing techniques and their applications in medicine - Ejsner, Rafal; Bilińska, Aleksandra; Marzec, Urszula; Załęski, Daniel (Quality in Sport, 2026)
The beginnings of 3D printing are estimated to date back to 1984. Since then, the technology has evolved significantly thanks to the development of software and a significant increase in computer power. 3D technology is used in many areas of orthopedic medicine. From the production of bone models, implants and the creation of drugs. Thanks to the development of software and biological materials, it is possible to create personalized patient implants or create much more accurate models than using single MRI or CT images in order to better plan the treatment procedure. Currently, materials made of paper, metal, ceramics and hydroxyapatite are used. Unfortunately, the above technology has a number of disadvantages. Despite continuous development, the costs are often several times higher than when using traditional therapeutic methods. Additionally, the amount of materials that can be used is limited. Perhaps this will change in the future, because the technology itself offers promising possibilities that may allow for much more accurate, personalized treatment and faster recovery of patients.